Clinical features and outcome of 2009 influenza A (H1N1) virus infections in children with malignant diseases: a case-control study - Paganini, Hugo (2011)
Fil: Paganini, Hugo. Hospital de Pediatría Dr. Juan P. Garrahan. Departamento de Enfermedades Infecciosas; Argentina.